ChemInform Abstract: Cyclocarbopalladation/Cross‐Coupling Cascade Reactions in Sulfide Series: Access to Sulfur Heterocycles. Issue 47 (6th November 2014) - Castanheiro, Thomas; Donnard, Morgan; Gulea, Mihaela; Suffert, Jean
Abstract First time, cyclocarbopalladation/cross‐coupling cascade reactions are applied for the efficient synthesis of sulfur heterocycles in combination with both Stille and Suzuki—Miyaura cross‐coupling reaction.